Inequality, Relative Deprivation and Financial Distress: Evidence from Swedish Register Data - Paula Roth (Research Institute of Industrial Economics (IFN), 2020)
Several studies have linked rising insolvency rates to increasing inequality and argued that this might be explained by individuals' desire to "Keep up with the Joneses". Using unique administrative register data on individual insolvencies in Sweden, I test whether the probability to become insolvent is related to inequality in one's reference group or to one's income distance relative to peers. Identification relies on area fixed effects, an extensive set of background characteristics and varying the definition of relevant reference groups. I find that there is a positive relationship between inequality and insolvency, where a 10 percent increase in top incomes increases the individual probability to become insolvent by 12 percent.
Keywords: D14; D31; D63; D91; E21; 330; Inequality; Insolvency; Bankruptcy; Financial distress; Social interaction